Predictive markers for treatment response in metastatic KRASmutant non-small cell lung cancer (UCC Student Medical Journal, 2026)
Background: Non-small-cell lung carcinoma (NSCLC) represents 85% of all lung cancer cases, with Kirsten Rat Sarcoma Virus (KRAS) being the most commonly detected mutation. This study retrospectively reviews patient charts and databases to identify specific markers linked to favorable and poor responses to treatment in a tertiary care setting.Methods: Pre-treatment hematological, pathological, and biochemical data were gathered from 70 patients diagnosed with KRAS-mutant NSCLC at Cork University Hospital between January 1, 2017, and December 31, 2021. Patients were categorized by radiological response to treatment and progression-free survival (PFS). Statistical analysis was performed using SPSS v29, with parametric data expressed as mean (SD) and nonparametric data as median [IQR]. T-tests, Chi-squared tests, and Mann-Whitney U tests were employed, with a significance level of p